1994
DOI: 10.1111/j.1095-8649.1994.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between river flow and entry to the Aberdeenshire Dee by returning adult Atlantic salmon

Abstract: One hundred and nine returning adult salmon were radio‐tagged in the estuary of the Aberdeenshire Dee, Scotland between February and August 1985 to 1989 and the times when 62 fish entered the river were recorded. Elapsed times between tagging and river entry were significantly greater during periods of lower than average river flows in all months where there were sufficient data to allow statistical comparison. The degree of association between river entry and particular levels of river discharge rate varied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Individual fish within a population employ a range of behavioral tactics (Potts and Wootton 1984) in the face of annual and interannual variations of average conditions to which their run timing is adapted. To some extent, fish can adjust their run timing to compensate for annual variability in environmental conditions (e.g., temperature and flow ;Banks 1969;Jonsson 1991;Smith et al 1994;Quinn and Adams 1996;Trépanier et al 1996;Quinn et al 1997;Hodgson 2000;Keefer et al 2004b;Strange, in press). Salmonids can also adjust travel rates after entry into freshwater during their spawning migrations (Quinn et al 1997;Keefer et al 2004a;Hanson et al 2008).…”
mentioning
confidence: 99%
“…Individual fish within a population employ a range of behavioral tactics (Potts and Wootton 1984) in the face of annual and interannual variations of average conditions to which their run timing is adapted. To some extent, fish can adjust their run timing to compensate for annual variability in environmental conditions (e.g., temperature and flow ;Banks 1969;Jonsson 1991;Smith et al 1994;Quinn and Adams 1996;Trépanier et al 1996;Quinn et al 1997;Hodgson 2000;Keefer et al 2004b;Strange, in press). Salmonids can also adjust travel rates after entry into freshwater during their spawning migrations (Quinn et al 1997;Keefer et al 2004a;Hanson et al 2008).…”
mentioning
confidence: 99%
“…Discharge peaks late in the migration period of both groups, however, may activate the migration of remaining fish, as observed in 2002 (smolt) and 2004 (adults). Thus, at times of low seasonal flow, migration of both groups may be associated with freshets, but during higher flows, migration is independent of increases in flow (Smith et al, 1994;Davidsen et al, 2005). Similarly, the response of adults to either increasing or decreasing flow appears to depend on the stage of migration; increased flow can increase movement into a river from an estuary, whereas Atlantic salmon migrating within the river may prefer decreasing flow (Tr epanier et al, 1996;Erkinaro et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, although the definition of estuary entrance is unclear (because there is no fixed boundary), several studies have made inferences about the impact of fresh water on estuary entry from observations (variously telemetry studies in estuaries, or counters and traps close to the tidal limit). Movement through the estuary has been reported to be positively associated with flow increase (Huntsman 1948;Hayes 1953;Potter 1988;Alabaster et al 1991;Smith et al 1994;Jonsson et al 2007;Archer et al 2008). The attraction effects of increased flow have been reported to be strongest during periods of relative low flow (Clarke et al 1994;Smith et al 1994).…”
Section: Movement and Flow Responses In Estuariesmentioning
confidence: 99%
“…Movement through the estuary has been reported to be positively associated with flow increase (Huntsman 1948;Hayes 1953;Potter 1988;Alabaster et al 1991;Smith et al 1994;Jonsson et al 2007;Archer et al 2008). The attraction effects of increased flow have been reported to be strongest during periods of relative low flow (Clarke et al 1994;Smith et al 1994). Other studies have reported that the flow effect may be non-existent or undetectable (Banks 1969;Trépanier et al 1996;Solomon et al 1999;Karppinen et al 2004;Thorstad et al 2008).…”
Section: Movement and Flow Responses In Estuariesmentioning
confidence: 99%